The Power of a Simple Question - Berry, Arnold J. (Anesthesiology (Philadelphia), 2024)
The Prevalence of Hepatitis B Markers in Anesthesia Personnel. By Berry AJ, Isaacson IJ, Hunt D, Kane MA. Anesthesiology 1984; 60:6–9 The prevalence of hepatitis B viral markers has increased in some groups of medical workers who are exposed to blood from patients carrying the virus, but this has not been studied critically in physicians and others who administer anesthesia. Physician anesthesiologists (M.D.) and nurse anesthetists and anesthesia assistants (non-M.D.) at four university-affiliated hospitals were evaluated for hepatitis B markers as determined by seropositivity for hepatitis B surface antigen, antibody to the hepatitis B surface antigen, or antibody to the hepatitis B core antigen. In the 86 subjects (38 M.D., 48 non-M.D.) who represented 80.4% of possible participants, the overall prevalence of serologic markers of hepatitis B was 23.3%. The frequency did not differ between M.D. (23.7%) and non-M.D. (22.9%) groups or between men (20.3%) and women (26.9%). Of 81 subjects who had no clinical history of hepatitis, 16 (19.8%) had positive serologic markers. The frequency of seropositivity increased with time since graduation from medical school (M.D.) or nursing school or college (non-M.D.). The prevalence of serologic markers of hepatitis B virus in this study of anesthesia personnel is five to eight times that of the general population but is similar to that of other medical workers who frequently are exposed to blood.